A new species of Ferorhinella with an unusual pattern of sexual size dimorphism (Hemiptera, Cercopidae, Tomaspidinae) - Paladini, Andressa (Zootaxa, 2010)
The spittlebug genus Ferorhinella (Hemiptera: Cercopidae) was described by Carvalho & Webb (2004) based on type species Sphenorhina brevis Walker (1851). Fennah (1968) had previously consigned this species to the genus Tropidorhinella. However, we consider Ferorhinella to be a valid genus based on its small size and the distinctive shape of the male genitalia: the parameres broad apically with two subapical process and the aedeagus with a bifid apex S-shaped. The proportion of the head and the shape of the aedeagus and parameres are also quite unlike those of other genera of Cercopidae, including Tropidorhinella. Until now, Ferorhinella was a monotypic genus. Tropidorhinella has four species.